Total Factor Productivity Calculation of the Indonesian Micro and Small Scale Manufacturing Industry - Endang Rostiana; Horas Djulius; Gugum Mukdas Sudarjah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
The purpose of this research is to determine the total factor productivity (TFP) of Indonesia's micro and small-scale manufacturing industries. The production function estimation approach established by Levinsohn-Petrin as the basis for computing TFP is employed in this study, with value added as the dependent variable and the value of labor costs and capital value proxied by the value of investment as the independent variables. This study uses secondary data from the Central Statistics Agency (BPS), which includes 23 sub-sectors of Indonesia's micro and small scale manufacturing industries that are included in the 2-digit ISIC, with the exception of the ISIC code 19 sub-sector, and covers the years 2010 to 2019, excluding 2016. The TFP value in the micro-scale Indonesian manufacturing industry was often higher than the TFP value on the small scale, according to this study. This research also demonstrates that low-tech sub-sectors, such as the food processing industry, have low productivity. On a small size, the estimated TFP value shows a decreasing trend, but on a micro scale, the estimated TFP value indicates an increasing trend.